Modulus distribution in polyacrylonitrile-based carbon fiber monofilaments. (February 2020) - Chen, Liuyang; Hao, Lifeng; Liu, Sichen; Ding, Guoming; Sun, Xiaolu; Zhang, Wanshuo; Li, Fan; Jiao, Weicheng; Yang, Fan; Xu, Zhonghai; Wang, Rongguo; He, Xiaodong
Abstract: Modulus distribution in carbon fiber (CF) monofilament plays a key role in bridging the microscopic heterogeneous structures to the macroscopic mechanical properties, and is critical to understand its performance. Here, we present a quantitative measurement of the modulus distributions for a series of commercially available polyacrylonitrile (PAN)-based CFs (T300, T700S, T800H, T1000G and M40J from Toray) using plasma-assisted radius profiling method. The distribution, which is unique for each kind of CFs, shows a strong correlation to monofilament tensile properties. Based on the observations, we propose a mechanical model that reveals the dependence of the tensile strength of CF monofilament on the local modulus gradient and the local structural fluctuations. The work is a great improvement to the traditional skin-core model, and facilitates the design of high strength and high modulus CFs. The mechanical model can be generally applied to all kinds of fiber-shaped structures and materials. Graphical abstract: Image 1